2016
DOI: 10.2139/ssrn.2850876
|View full text |Cite
|
Sign up to set email alerts
|

Energy Affordability in the EU: The Risks of Metric Driven Policies

Abstract: This paper provides a pan-EU mapping of energy affordability using energy expenditure shares. Large variations in energy expenditure shares are identified, with the shares being significantly higher in New Member States than the EU15. First, these variations indicate that a single expenditurebased pan-EU fuel poverty metric is problematic; there is a trade-off between a metric identifying households in most need within individual Member States and one identifying households in a similar position across Member … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Lawson et al (2015) obtain similar results for New Zealand. Moreover, Waddams and Deller (2017) for UK and Deller (2018) for the EU found that the identification of a common fuel poverty metric based solely on spending criteria is problematic due to heterogeneity between countries. More recently, Fizaine and Kahouli (2018) analyse the use of several objective and subjective measures to categorise fuel poverty and find differences in the profiles of the households depending on the measure and threshold utilised.…”
Section: Introductionmentioning
confidence: 99%
“…Lawson et al (2015) obtain similar results for New Zealand. Moreover, Waddams and Deller (2017) for UK and Deller (2018) for the EU found that the identification of a common fuel poverty metric based solely on spending criteria is problematic due to heterogeneity between countries. More recently, Fizaine and Kahouli (2018) analyse the use of several objective and subjective measures to categorise fuel poverty and find differences in the profiles of the households depending on the measure and threshold utilised.…”
Section: Introductionmentioning
confidence: 99%
“…A pan-EU map of energy affordability, based on energy expenditures shares, shows large variations across the EU which questions the appropriateness of a pan-EU fuel poverty metric (Deller 2016). Deller (2016) concludes that the best way that the European Commission can support policy synergy is by making available high-quality data on pan-EU energy affordability and collating robust impact assessments that identify effective policy interventions. As we describe below, this type of data is lacking.…”
Section: Defining Energy Povertymentioning
confidence: 99%
“…Figure 1 of Deller (2018) provides an overview of how energy affordability (FP) measures can be split between: (i) ENEX indicators, (ii) self-reports of the lived experience, and (iii) proxy indicators. While Deller (2018) and Tirado Herrero (2017) caution against focusing excessively on a single FP metric/definition, Thomson et al (2016) highlight the appeal of headline statistics to galvanise political action; while Thomson et al (2017) and Tirado Herrero (2017) provide overviews of alternative FP measurement approaches in the European context. 16 This broader debate has been influenced by changing official expenditure-based FP metrics in the UK, and the need to utilise perception-based metrics for pan-EU assessments of FP.…”
Section: Existing Literaturementioning
confidence: 99%